The readiness of the agricultural sector to adopt the internet of things: a case of Western Cape, South Africa - Soeker, Inaam (Department of Information Systems, 2025)
Background: Food scarcity arising from climate change has garnered widespread recognition as a critical global concern, necessitating serious attention. Far-reaching impacts of climate change extend across dimensions such as the environment, technology, policy, and societal progress. Among these dimensions, the implications for food production within the agricultural sector is significant. With the expanding global population, the demand for agricultural output intensifies, exerting unprecedented pressure on the industry to meet this growing need. As a result, the agricultural sector is confronted with the imperative to transition towards sustainable farming practices to enhance overall productivity. Amid this imperative, the integration of technology, particularly the Internet of Things (IoT), emerges as an indispensable solution. Extensive research demonstrates that IoT implementation in agriculture yields manifold benefits, including enhanced food production, increased productivity, and bolstered sustainability. Moreover, IoT equips farmers with tools to navigate the complex challenges posed by climate change and food scarcity, ensuring their competitiveness and profitability. However, a pivotal consideration is the readiness of the agricultural sector to implement IoT. Purpose of the Research: Despite the considerable potential gains, the readiness of the South African agricultural sector to adopt IoT remains a less-explored area. This study aims to address this gap by examining the landscape of IoT adoption readiness within the context of the South African agricultural sector. Design/Methodology/Approach: To evaluate readiness to adopt IoT, a qualitative research method was adopted in this research and an analysis was methodically employed. This multifaceted analysis approach encompassed distinct dimensions— political, environmental, social, and technological (PEST). Each dimension was assessed to ascertain its strengths, weaknesses, opportunities, and threats (SWOT), in the context of IoT integration within the agricultural sector. This systematic PEST-SWOT analysis culminated in positioning the readiness of the agricultural sector in South Africa. Findings: The findings of this study unveil a notable duality in South Africa's developmental landscape. This dichotomy becomes apparent through the coexistence of both developed and developing facets. This division manifests in distinct states. On the one hand, the developed portion of the agricultural sector exhibit a tangible readiness for IoT adoption. On the other hand, the developing portion encounter barriers that necessitate comprehensive mitigation of inherent weaknesses and threats resulting in its unpreparedness for adopting IoT. This division closely mirrors the distinction between the commercial and SME sectors, embodying the readiness of the developed state and lack of readiness in the developing state, respectively. This inherent dichotomy, rooted in historical challenges, underscores the urgency for holistic resolutions. Overall, the findings suggest that the South African agricultural sector is not ready for IoT adoption. Practical Implications: The practical implication of this research underscores the vital need for tailored strategies that bridge the readiness gap between the developed and developing portion of the agricultural sector. Addressing the distinctive challenges faced by each portion, particularly considering their historical contexts, will be instrumental in fostering a cohesive and synchronised path towards embracing IoT. Originality/Contribution: The contribution of this study lies in its comprehensive examination of readiness to adopt IoT within the South African agricultural sector. By employing a multi-dimensional PEST-SWOT analysis, this research not only sheds light on the nuanced landscape of IoT adoption but also positions the readiness of the Western Cape's agricultural sector in a holistic context. This approach offers a unique lens through which to understand the intricate challenges and opportunities that IoT adoption presents in this critical sector.